Displasia cleidocraniana: revisão e estudo das características clínicas e radiográficas de uma família chilena - Alejandra Castro Araya; Enrico Escobar López; Gloria García Moreno (Revista de Odontopediatria Latinoamericana)
Cleidocranial Dysplasia (CDD) is a rare syndrome usually caused by an autosomical dominant gene with high penetrance and variable degree of expressions. This condition is usually caused by a mutation of the Core Binging Factor-1 gene, located at chromosome 6p21. This gene encodes a protein necessary for the correct functioning of osteoblast cells, however, 40% of cases of CDD appear spontaneously with no apparent genetic cause. CDD Primarily affecting bones undergoing intramembranous ossification characterized by clavicular aplasia or hypoplasia, retarded cranial ossification, multiple impacted permanent teeth, supernumerary teeth, short stature, delayed closure of the sagittal fontanelles and a variety of other skeletal abnormalities. A family case of CDD is presented. A mother and two children were referred to the Oral Pathology Service of the University of Chile. In all three cases, a radiological series was performed over the entire body. Generalized dysplasia in bones (clavicular aplasia), prolonged retention of primary teeth and delayed eruption of permanent, as well as supernumerary teeth was diagnosed. Clinical and Radiological findings are presented.